Soundscape Analysis of Selected Landforms on Spitsbergen - CZOPEK, Dorota; MAŁECKI, Pawel; PIECHOWICZ, Janusz; WICIAK, Jerzy (Archives of Acoustics, 2019)
This article shows acoustic measurements from Svalbard archipelago in the Arctic, located in the Arctic Ocean. The aim of the research was to show the Svalbard soundscape as well as to record and analyse the spatial-temporal dynamics of the acoustic environment, the human impact on the soundscape and to collect baseline data for future comparative research. Svalbard is interesting for many science disciplines because it has an arctic climate and, at the same time, it is relatively easily accessible. Climatologists, geologists, glaciologists, biologists and even anthropologists could find interesting themes to investigate here. Additionally, the soundscape of Spitsbergen is worthy of detailed examination. This paper presents comparative analysis of the soundscape of various spots near Longyearbyen in Management Area 10. The soundscape analysis of selected valleys shows the strong influence of human activity on the soundscape as well as the variability and characteristic features of the natural Arctic soundscape.